FT-IR, Thermal and Optical Studies of Gel Grown Cobalt Tartrate Crystals - S.J. Nandre; S.J. Shitole; R.R. Ahire (Журнал нано- та електронної фізики)
The growth of cobalt tartrate crystals was achieved in silica gel by single diffusion method. Optimum conditions were established for the growth of good quality crystals. Fourier transform infrared (FT-IR) spectroscopic study indicates the presence of water molecules and suggests that tartrate ions are doubly ionized. The thermal behavior of the material was studied using thermogravimetry (TG) and differential thermal analysis (DTA). The results show that the material is thermally stable up to30 C, beyond which it decomposes through many stages till the formation of cobalt oxide at 995 C. The non linear optical behavior of these crystals is reported and explained.